Pengaruh Manajemen Rantai Pasokan Terhadap Kinerja UMKM dengan Keunggulan Kompetitif Sebagai Variabel Mediasi - Novita Nazilaturrohmah; Wijayanti Wijayanti; Ishak Ishak (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The rapid economic development in Indonesia has intensified competition within the MSME sector. Traditional retail MSMEs in Kutoarjo District face various challenges, including the limited implementation of supply chain management and difficulties in competing with modern retail businesses that operate with integrated business systems. One strategy that can be implemented to improve MSME performance is through effective supply chain management and the development of sustainable competitive advantage. This study aims to examine the mediating role of competitive advantage in the relationship between supply chain management and the performance of traditional retail MSMEs in Kutoarjo District. The population of this study consisted of all retail MSME owners in Kutoarjo District. The sampling technique used was purposive sampling, with a total sample of 100 respondents. This research employed a survey design, and data were collected through questionnaires using a Likert scale. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS software. The results of this study indicate that: (1) supply chain management has a positive effect on MSME performance; (2) supply chain management has a positive effect on competitive advantage; (3) competitive advantage has a positive effect on MSME performance; and (4) competitive advantage mediates the effect of supply chain management on MSME performance in traditional retail MSMEs in Kutoarjo District.